Effect of Dates Consumption On Bleeding, Duration, And Types of Labor - Kuswati Kuswati; Rohmi Handayani (Faculty of Medicine, Universitas Andalas, 2019)
Dates are a good source of nutrition for the body if consumed regularly both in the form of dried fruit, wet, as well as in the form of palm juice extracts, especially for pregnant and maternal mothers. Pregnant women who are going to give birth are in desperate need of drinks and foods that are rich in sugar, this is because of the many contractions of the uterine muscles when it comes to removing the baby, especially if it takes a long time. Dates contain potuchin hormone which functions to bind the uterus and muscles of the uterus so that it can help reduce postpartum bleeding. Besides, there is the hormone oxytocin which can help stimulate contractions in the muscles of the uterus so as to facilitate labor. The purpose of this study was to determine the effect of consumption of dates on bleeding, length of labor and type of labor. This type of research is a Pre experiment with a post-test Only Control Group Design research design. The population in this study were all pregnant women in the working area of South Klaten Public Health Center with estimated deliveries from July to September 2018. While the sample size was 60 samples consisting of 30 treatment group respondents and 30 control group respondents. The sampling technique used in this study was Quota sampling. Data analysis using Fisher Exact test and Mann-Whitney U test with p-value considered significant is p = 0.05. The results of the study of bleeding showed that there were no significant differences in the estimation of blood loss and during labor and type of delivery between the treatment group and the control group (p-value = 0.5). The results of the study about the length of labor showed that there was an effect of date consumption on the length of labor, with a value of p = 0,000